Coprecipitation of curcumin/PVP with enhanced dissolution properties by the supercritical antisolvent process. (March 2019) - Matos, Ravenna Lessa; Lu, Tiejun; Prosapio, Valentina; McConville, Christopher; Leeke, Gary; Ingram, Andrew
Highlights: Curcumin/PVP coprecipitates were produced from acetone-ethanol mixtures by SAS. Acetone percentage has great influence on particle size and product recovery. Nanoparticles (51–96 nm) and sub-microparticles (117–327 nm) were obtained. Curcumin recovery, crystallinity, release profile and degradation were measured. The apparent solubility of coprecipitates increased more than 600 times. Abstract: The poor solubility of curcumin (CURC) in aqueous media leads to a low bioavailability, which prevents its application in pharmaceutical formulations. In this work, the Supercritical Antisolvent process (SAS) was used to produce coprecipitates of CURC and poly (vinyl pyrrolidone) (PVP) from mixtures of ethanol and acetone. The effects of operating parameters: pressure, temperature, solution concentration, drug/polymer mass ratio and solution flow rate were analysed for a 70–30 (v/v) acetone-ethanol mixture. It was found that the composition of acetone in the solvent mixture is the parameter that affects particle size and curcumin recovery the most. The thermal behaviour, crystallinity, molecular interactions, apparent solubility, release profile of the coprecipitates and possible degradation of curcumin were investigated. The results showed that the SAS process is effective in preparing amorphous formulations of CURC/PVP with an apparent solubility of more than 600 times higher than that of the physical mixture of the raw compounds.